Genetic variation and heritability of agronomic traits in a native perennial forage species from drylands: breeding potential of Festuca pallescens - Guidalevich, Verónica; Berro, Inés; Aparicio, Alejandro Gabriel; Azpilicueta, Maria Marta; Lopez, Aldana Soledad; Arias Rios, Jorge Andres; Picasso, Valentin; Gutierrez, Lucia; Marchelli, Paula (Springer Nature, 2025)
Festuca pallescens is a native forage grass species of Patagonia, playing a crucial role in supporting sheep production in arid and semi-arid ecosystems. This study assessed genetic differentiation among populations and estimated the heritability of traits linked to biomass production and phenological development as part of its domestication effort. A common garden trial was established with ten half-sib families from four preselected populations, and phenological and morphological traits were measured over three seasons. Trait correlations were analyzed, and a mixed model approach was employed to estimate Wright’s QST and narrow-sense heritability. QST estimates ranged from 0.18 to 0.47 for phenological traits and from 0.086 to 0.093 for morphological traits; heritability values ranged from 0.33 to 0.78 for phenological traits and from 0.27 to 0.50 for morphological traits. Results indicate strong genetic structure for most phenological traits, suggesting diversifying selection. A population effect and within-population variability were also observed for most traits, highlighting potential for genetic improvement. We propose selection strategies to establish a breeding program for this species, aiming to develop adapted synthetic varieties with greater fitness. These new varieties could enhance forage productivity and potentially be applied in regions with similar climatic and environmental conditions.